One nation under debt : Hamilton, Jefferson, and the history of what we owe - Wright, Robert E. (Robert Eric), 1969- (New York : McGraw-Hill, 2008)
The United States was born in debt, a debt so deep that it threatened to destroy the young nation. Thomas Jefferson considered the national debt a monstrous fraud on posterity, while Alexander Hamilton believed debt would help America prosper. Both, as it turns out, were right. This book explores the untold history of America's first national debt, arising from the immense sums needed to conduct the Revolution. Financial historian Wright recounts the key events that shaped the U.S. financial system and explains how the actions of our forefathers laid the groundwork for the debt we still carry today.--From publisher description.
A twinkle in the eye : the importance of government debt -- Parentage : European precedents -- Conception : financing revolution -- Gestation : the Constitution and the national debt -- Birth : Alexander Hamilton's grand plan -- Youth and maturity : the public debt grows up, then slims down -- Life : the life and times of federal bondholders in Virginia -- Blessings : American economic growth -- Death and reincarnation : Jackson's triumph and failure.
Includes bibliographical references (p. 371-386) and index.
Includes bibliographical references and index.
Keywords: Debts, Public -- United States -- History -- 18th century; Budget deficits -- United States -- History -- 18th century; Government spending policy -- United States -- History -- 18th century; Debts, Public -- United States -- History -- 19th century; Budget deficits -- United States -- History -- 19th century; Government spending policy -- United States -- History -- 19th century; United States -- Economic conditions -- To 1865.; Hamilton, Alexander, -- 1757-1804.; Jefferson, Thomas, -- 1743-1826.; Computer network resources